Management of vault prolapse. (12th July 2013) - Ramalingam, K; Monga, Ash
Abstract : Key content: Vaginal wall prolapse is increasing in incidence with improvement in life expectancy. Conservative and surgical treatments exist. Treatment should be tailored to individual needs depending on prolapse symptoms, sexual function and co‐existing medical conditions. Indications, expertise required and complications of different procedures should be explored with available evidence. Learning objectives: Recognise the presentation of vaginal vault prolapse. Learn about different options available for the treatment of vaginal vault prolapse. Understand the limitations and complications of different procedures and counsel patients appropriately. Ethical issues: Should procedures that improve quality of life be performed in elderly patients with comorbid conditions? Should simpler surgical treatments such as colpocleisis or vaginal surgery be performed to be more cost‐effective compared with laparoscopic or robotic procedures? How safe is it to use mesh in vault prolapse by the abdominal or vaginal route?